2019
DOI: 10.1016/j.biomaterials.2018.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation increases hypertrophy and metabolic flux in tissue-engineered human skeletal muscle

Abstract: In vitro models of contractile human skeletal muscle hold promise for use in disease modeling and drug development, but exhibit immature properties compared to native adult muscle. To address this limitation, 3D tissue-engineered human muscles (myobundles) were electrically stimulated using intermittent stimulation regimes at 1 Hz and 10 Hz. Dystrophin in myotubes exhibited mature membrane localization suggesting a relatively advanced starting developmental maturation. One-week stimulation significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
142
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(158 citation statements)
references
References 115 publications
9
142
1
Order By: Relevance
“…Higher levels of resistance are likely to provide more load to the muscles, leading to more effective myophysiological changes, but this can lead to rapid muscle fatigue and even temporary pain. Resistance training increases the number of myofibres, which causes muscle hypertrophy, and a concomitant increase in strength . Previous studies have shown resistance training in swallow‐related muscles, including tongue muscle, have resulted in increased muscle strength and thickness, similar to the results of this study.…”
Section: Discussionsupporting
confidence: 88%
“…Higher levels of resistance are likely to provide more load to the muscles, leading to more effective myophysiological changes, but this can lead to rapid muscle fatigue and even temporary pain. Resistance training increases the number of myofibres, which causes muscle hypertrophy, and a concomitant increase in strength . Previous studies have shown resistance training in swallow‐related muscles, including tongue muscle, have resulted in increased muscle strength and thickness, similar to the results of this study.…”
Section: Discussionsupporting
confidence: 88%
“…Resistance training that provides effective loads increases the thickness of skeletal muscles. This effect is associated with an increase in the number of myofibers and consequently an increase in thickness, which is called muscle hypertrophy . Previous studies investigating healthy adults have reported physiological changes in muscles, including in the muscle thickness and cross‐sectional area, caused by resistance training of the limbs .…”
Section: Discussionmentioning
confidence: 99%
“…Whereas decreased half relaxation time has been outlined to be indicative of calcium re-uptake in the SR via the SERCA pump, with increased SERCA1 mRNA transcription evident following electrical stimulation of 3D muscle tissue. 45 Both functional measures were significantly decreased in time following innervation, indicating an enhanced efficiency of the molecular mechanisms of muscle contraction. Importantly, neuromuscular tissues using primary rat cells reported increases in time to peak force and half relaxation time measures upon innervation, suggesting that alterations in the excitability of bioengineered motor units appears sensitive across species.…”
Section: Discussionmentioning
confidence: 96%